Real-Life Retention Rates and Reasons for Switching of Biological DMARDs in Rheumatoid Arthritis, Psoriatic Arthritis, and Ankylosing Spondylitis - Bhushan, Vandana; Lester, Susan; Briggs, Liz; Hijjawi, Raif; Shanahan, E. Michael; Pontifex, Eliza; Ninan, Jem; Hill, Catherine; Cai, Fin; Walker, Jennifer; Goldblatt, Fiona; Wechalekar, Mihir D. (Frontiers in Medicine, 2021)
Aims: To determine real-life biologic/targeted synthetic disease-modifying anti-rheumatic drug (b/tsDMARD) retention rates in rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS), explore reasons for switching and to compare results to previously published data. Methods: Time-to-event analysis for mean treatment duration (estimated as the Restricted Mean Survival Time), bDMARD failure, and b/tsDMARDs switching was performed for 230 patients (n= 147 RA, 46 PsA, 37 AS) who commenced their first bDMARD between 2008–2018. Patients were managed in a dedicated ‘biologics’ clinic in a tertiary hospital; the choice of bDMARD was clinician driven based on medical factors and patient preferences. The effect of covariates on switching risk was analysed by a conditional risk-set Cox proportional-hazards model. Treatment retention data was compared to a historical analysis (2002-2008). Results: The proportions remaining on treatment (retention) were similar, throughout follow-up, for the first, second and third b/tsDMARDs across all patients (p = 0.46). When compared to RA patients, the risk of bDMARD failure was halved in PsA patients (Hazard Ratio (HR) = 0.50), but no different in AS patients (HR = 1.0). The respective restricted mean (95%CI) treatment durations, estimated at 5 years of follow-up, were 3.1 (2.9, 3.4), 4.1 (3.7, 4.6), and 3.3 (2.8, 3.9) years, for RA, PsA, and AS, respectively. Age, gender, disease duration, smoking status and the use of concomitant csDMARDS were not associated with the risk of bDMARD failure. The most common reasons for switching in the first and subsequent years were secondary (n = 62) and primary (n = 35) failure. Comparison with historical data indicated no substantive differences in switching of the first biologic for RA and PsA. Conclusion: Similar retention rates of the second and third compared to the first bDMARD in RA, PsA and AS support a strategy of differential bDMARD use informed by patient presentation. Despite greater availability of b/tsDMARDs with differing mechanisms of action, retention rates of the first bDMARD remain similar to previous years.